2008
DOI: 10.1152/japplphysiol.90476.2008
|View full text |Cite
|
Sign up to set email alerts
|

Age-related medial elastocalcinosis in arteries: mechanisms, animal models, and physiological consequences

Abstract: Atkinson J. Age-related medial elastocalcinosis in arteries: mechanisms, animal models, and physiological consequences. J Appl Physiol 105: 1643-1651, 2008. First published September 4, 2008 doi:10.1152/japplphysiol.90476.2008.-With age, the calcium content of the arterial wall increases. Calcification occurs at two main levels: intimal plaques and the medial elastic fiber network. The latter has been referred to as medial elastocalcinosis and is the subject of this review. The mechanisms involved in elastoca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
62
0
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(67 citation statements)
references
References 126 publications
3
62
0
2
Order By: Relevance
“…Arterial aging results in progressive stiffening of the arteries, and the mechanisms underlying this phenomenon have been reported in-depth pathophysiologically 26,27) . Although normal arterial stiffening occurs in individuals in association with age, some risk factors hasten this process 28,29) .…”
Section: Discussionmentioning
confidence: 99%
“…Arterial aging results in progressive stiffening of the arteries, and the mechanisms underlying this phenomenon have been reported in-depth pathophysiologically 26,27) . Although normal arterial stiffening occurs in individuals in association with age, some risk factors hasten this process 28,29) .…”
Section: Discussionmentioning
confidence: 99%
“…Longstanding arterial pulsation in the central artery causes elastin fiber fatigue and fracture. Endothelial dysfunction 21) , the accumulation of advanced glycation end products on proteins 22) , the calcium content of the arterial wall 22) , changes in the extracellular matrix expression 23,24) and increased stiffness of vascular smooth muscle cells 23,24) have been reported to mediate age-associated vascular stiffness.…”
Section: Age-specific Cavi Scores In the Cvd Risk-free Healthy Subjectsmentioning
confidence: 99%
“…14,22 Measures of body size have been found to be positively associated with blood estrogen levels in postmenopausal women 23 because estrogen levels may become elevated as a result of aromatization of androgens in adipose tissue. We found that older postmenopausal woman with a larger body size had a lower probability of having BAC than women of the same age with a smaller body size.…”
Section: Biological and Sociological Factorsmentioning
confidence: 99%